Hanging ability in climbing: an approach by finger hangs on adjusted depth edges in advanced and elite sport climbers - Bergua, P.; Montero-Marin, J.; Gomez-Bruton, A.; Casajús, J. A. (International Journal of Performance Analysis in Sport, 2018)
Hanging ability on small depth edges is one of the most limiting factors in climbing. The aim of this study was to assess the reliability and validity of a hanging ability indicator measured on an adjusted depth edge. Forty voluntary sport climbers (34 men) were divided into an advanced group (AG; n = 22) and an elite group (EG; n = 18). Climbers performed three sustained finger tests following a test-retest design: (a) maximum hanging time on a 14-mm edge depth (MHT_14), (b) minimum edge depth in which climbers could hang for 40 s exactly (MED_40) and (c) maximum added weight test on the MED_40 edge depth (MAW_5). EG performed better than AG in all tests. The regression analyses showed that the MHT_14 test and MAW_5 test explained a 35% and 69% of the climbing sport level in AG and EG, respectively. All the tests were reliable (ICC3,1 values ranging from 0.89 to 1.00). The MAW_5 and MHT_14 tests demonstrated to be valid and reliable hanging ability indicators for EG and AG, respectively. The measurement of hanging ability on adjusted depth edges might be a key factor in elite climbers, but not necessary in lower level climbers.